2013
DOI: 10.1039/c3cc43432j
|View full text |Cite
|
Sign up to set email alerts
|

A thermally healable polyhedral oligomeric silsesquioxane (POSS) nanocomposite based on Diels–Alder chemistry

Abstract: A novel, tough, transparent, self-healing POSS nanocomposite material was prepared through a thermally reversible Diels-Alder (DA) reaction between furan-end functionalized POSS and bismaleimide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 13 publications
0
59
1
Order By: Relevance
“…And the free Si O cage absorbs the energy during impact and eliminates effect of atomic oxygen. And more specifically, compared with other reinforcements such as SiO 2 and Al 2 O 3 , the organic group outside Si-O cage is able to absorb energy, which helps the small initial cavity induced by atomic oxygen to recover before expansion [22]. It has been proven that the atomic oxygen resistance of Kapton is quadrupled after reinforced by POSS at atomic oxygen fluence of 2 × 10 20 atoms/cm 2 .…”
Section: Simulation Results Of Atomic Oxygen Erosion Of Poss/pvdf Commentioning
confidence: 99%
“…And the free Si O cage absorbs the energy during impact and eliminates effect of atomic oxygen. And more specifically, compared with other reinforcements such as SiO 2 and Al 2 O 3 , the organic group outside Si-O cage is able to absorb energy, which helps the small initial cavity induced by atomic oxygen to recover before expansion [22]. It has been proven that the atomic oxygen resistance of Kapton is quadrupled after reinforced by POSS at atomic oxygen fluence of 2 × 10 20 atoms/cm 2 .…”
Section: Simulation Results Of Atomic Oxygen Erosion Of Poss/pvdf Commentioning
confidence: 99%
“…One example is curing epoxy-POSS units with conventional curing agents to result in epoxy resin/POSS nanocomposites [22]. Another example reported with Xu et al is to crosslink the furan-modified POSS molecules with a bismaleimide compound through the maleimide-furan DielseAlder (DA) reaction so as to result in self-healing POSS-based nanocomposites [23].…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mechanism between MMA-POSS and FA has been firstly examined in this work. On the other hand, the DA reaction is thermally reversible and has been widely utilized in building up self-healing polymeric materials [23e26], including the Xu's pioneer work on POSS-based self-healing nanocomposites [23]. As a result, the obtained MMA-POSS/FA nanohybrids materials could also exhibit self-healing property.…”
Section: Introductionmentioning
confidence: 99%
“…The self-healing potential of BMIs has also been combined with nanocomposite technology. Xu et al demonstrated that it is possible to functionalise a POSS molecule with furan groups via an epoxide-containing intermediate [150]. This material was capable of undergoing crack healing at 135 -150 °C, however it was noted that scratches on such a material could not be replenished due to the removal of necessary material.…”
Section: Bismaleimides In Self-healing Thermosetsmentioning
confidence: 99%